A will for the woods [videorecording (DVD)] ([Publisher not identified], 2014)
While battling lymphoma, Clark has discovered a burgeoning movement that uses burial to conserve and restore natural areas, forgoing typical funeral practices that stress the ecosystem. Boldly facing his mortality, Clark and his partner Jane have become passionate about green burial, compelled by both the environmental benefits and the idea that one can remain within the cycle of life, rather than being cut off from it.